MODERN OPERATING CONDITIONS OF THE SUPPLY CHAIN SYSTEM AT LIGHT INDUSTRY ENTERPRISES OF UKRAINE AND OPPORTUNITIES FOR THEIR DEVELOPMENT (Development Service Industry Management, 2025)
The article examines the current conditions of the supply chain system functioning using the example of light industry enterprises in Ukraine. The current socio-economic conditions of the management of Ukrainian light industry enterprises are studied. The essence and elements of the light industry system in Ukraine are revealed. The features of the formation and functioning of supply chains in light industry are considered. The impact of full-scale hostilities on the light industry of Ukraine is studied. The impact of such factors as occupation, mobilization and changes in logistics routes on supply chains in the light industry of Ukraine is considered. The dynamics of the number of light industry enterprises is analysed, the volume of cargo transportation in Ukraine is studied. Potential ways for the development of light industry are considered, and opportunities for the development of supply chains at Ukrainian enterprises are presented.
Keywords: supply chains; light industry; logistics; management; cargo transportation